A highly efficient broadband multi-functional metaplate. Issue 7 (8th March 2023) - Satti, Azhar Javed; Naveed, Muhammad Ashar; Javed, Isma; Mahmood, Nasir; Zubair, Muhammad; Mehmood, Muhammad Qasim; Massoud, Yehia
Abstract : Due to the considerable potential of ultra-compact and highly integrated meta-optics, multi-functional metasurfaces have attracted great attention. Abstract : Due to the considerable potential of ultra-compact and highly integrated meta-optics, multi-functional metasurfaces have attracted great attention. The mergence of nanoimprinting and holography is one of the fascinating study areas for image display and information masking in meta-devices. However, existing methods rely on layering and enclosing, where many resonators combine various functions effectively at the expense of efficiency, design complication, and complex fabrication. To overcome these limitations, a novel technique for a tri-operational metasurface has been suggested by merging PB phase-based helicity-multiplexing and Malus's law of intensity modulation. To the best of our knowledge, this technique resolves the extreme-mapping issue in a single-sized scheme without increasing the complexity of the nanostructures. For proof of concept, a multi-functional metasurface built of single-sized zinc sulfide (ZnS) nanobricks is developed to demonstrate the viability of simultaneous control of near and far-field operations. The proposed metasurface successfully verifies the implementation of a multi-functional design strategy with conventional single-resonator geometry by reproducing two high-fidelity images in the far field and projecting one nanoimprinting image in the near field. This makes the proposed information multiplexing technique a potential candidate for many high-end and multi-fold optical storage, information-switching, and anti-counterfeiting applications.